Rencana Pengembangan CSSD (Central Sterile and Supplies Department) Berdasarkan Kebutuhan di RS Meilia Tahun 2015 - Delia, Lintang Kusuma (UI Scholars Hub, 2016)
To meet the requirements of Peraturan Menteri Kesehatan RI number 56 2014 and JKN in 2015, RS Meilia need the planning of CSSD development that refers to the literature, regulations, guidelines and standards of the Ministry of Health of Indonesia and also refers to the analysis of internal and external factors in the RS Meilia CSSD to reach an ideal CSSD. The analytical results are RS Meilia has been preparing since the beginning of the construction of the hospital to hold a separate CSSD unit. In addition, there is a problem about the distribution flow of dirty goods and sterile goods are still mixed.CSSD development plan was divided into three stages. The first stage should be done as it relates to accreditation of hospitals, namely the separating distribution flow of sterile goods and dirty goods. The second stage is the development steps of CSSD with conditions still remain below the unit OK, namely human resources development, renewing and socialization of SPO to CSSD staff, unit OK and other units, improving the maintenance of CSSD sterilization machines, and create a standard label for the sterile goods. While third stage is the steps that must be done when the development of the CSSD into the unit itself, which is the renovation of OK and CSSD facilities, the recruitment of head of unit and sub-unit, and adding other CSSD equipment.